Appropriate Resistance Intensity and Effective Exercise for Activation of Infraspinatus - Yu, Il-Young; Oh, Se-Il; Jung, Won-Jeong; Oh, Jaeseop (International Journal of Sports Medicine, 2019)
We investigated the muscle activities of the infraspinatus and posterior deltoid, as well as the ratio of the infraspinatus to posterior deltoid muscle activities, in response to 3 resistance intensities during prone external rotation (PER) and sitting external rotation (SITER) exercises. Fifteen healthy males participated; the subjects performed two exercises randomly at three resistance intensity levels: 1) low intensity (10–20%); 2) medium intensity (45–55%); 3) high intensity (60–70%). Surface electromyography was used to measure the activities of the infraspinatus and posterior deltoid muscles. The activities of the infraspinatus and posterior deltoid increased significantly as the resistance intensity increased during both PER and SITER exercises (p<0.001). The infraspinatus-to-posterior deltoid activity ratio increased as the resistance intensity decreased. Whereas the muscle activity ratio was highest under low and medium intensity during PER and SITER, respectively, and the muscle activity ratio was significantly increased at medium intensity compared with high intensity during both PER (p=0.023) and SITER (p=0.001). Our results suggest that low to medium intensity is the appropriate resistance intensity for selective activation of the infraspinatus. In addition, our results suggest that PER and SITER are effective for strengthening the infraspinatus.
Keywords: infraspinatus; selective activation; resistance intensity; electromyography